A California Correction? Legislature Will Consider Allowing Attorney Malpractice Proof from Mediation. Issue 7 (18th July 2017) - Kichaven, Jeff
Abstract : The evidence is in. After 43 years of federal practice under Rule 408 of the Federal Rules of Evidence (1975); 19 years of New York practice under CPLR 4547 (1998); and 16 years of practice in various states under the Uniform Mediation Act (2001), we can conclude: Statutory confidentiality is not necessary for effective mediation.